2002
DOI: 10.1016/s0735-1097(02)01966-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical outcome of iatrogenic femoral arteriovenous fistulas

Abstract: Almost 1% of patients undergoing cardiac catheterization acquire femoral AVF, for which patient- and procedure-related risk factors could be identified. One-third of iatrogenic AVF close spontaneously within one year. Cardiac volume overload and limb damage are highly unlikely with AVF persistence. Thus, a conservative management for at least one year seems to be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 19 publications
2
107
0
8
Order By: Relevance
“…4,5) AVF may be relatively asymptomatic with bruising and small haematomas in the acute phase attributed to the percutaneous intervention. However chronic arteriovenous fistula may present with symptoms of intermittent claudication due to the steal phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5) AVF may be relatively asymptomatic with bruising and small haematomas in the acute phase attributed to the percutaneous intervention. However chronic arteriovenous fistula may present with symptoms of intermittent claudication due to the steal phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) One third of all arteriovenous fistula close spontaneously in one year, and hence, there is some evidence to manage asymptomatic arteriovenous fistula conservatively by a wait and watch policy before initiating any treatment. 4) Endovascular techniques have the advantage of being a minimally invasive intervention with reduced patient morbidity and in-patient stay. Covered stents help exclude the fistula from the arterial blood flow and thus results in thrombotic occlusion of the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Ona je veoma retk i njena incidenca iznosi do 0.86 % (15). Zbog periferne lokalizacije najčešće se manifestuje lokalnim simptomima na mestu kanulacije u vidu šuma, palpatornog trila i otoka ekstremiteta.…”
Section: Dijagnoza I Klinička Slikaunclassified
“…Za razliku od pseudoaneurizmi za spontano zatvaranje arteriovenskih fistula je neophodno duže vreme. Kelm 15 je u svojoj studij konstatovao da se 38 % fistula spontano zatvorilo unutar godinu dana.…”
Section: Lečenjeunclassified
“…It has been also demonstrated that the puncture of the superficial or deep femoral artery below the bifurcation of the common femoral artery is strongly associated with the formation of femoral AVFs following cardiac catheterization [5,6]. A reduced blood flow in the downstream vascular bed and heart failure due to cardiac volume overload have been demonstrated as potential adverse effects of traumatic AVFs [7], but it has been reported that these adverse effects are highly unlikely in patients with femoral AVFs following cardiac catheterization [3]. The present case also had never experienced any adverse effects of the AVF.…”
mentioning
confidence: 99%